2022
DOI: 10.1155/2022/7686405
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin A Intake and Circulating Vitamin A Concentrations and the Risk of Three Common Cancers in Women: A Meta-Analysis

Abstract: Background. According to relevant clinical research, dietary and circulating antioxidants vitamin A are connected with the risk of breast, cervical, and ovarian cancer in women. However, there was inconsistency between the findings. We completed this meta-analysis at the right moment to address this contradiction of the problem. Methods. Web of Science, Embase, and PubMed databases were searched using the proposed search strategy and filtered using the inclusion and exclusion criteria as well as the NOS qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Vitamin A deficiency can cause diseases such as decreased immunity, night blindness, dry skin, diarrhea, and certain cancers, including breast cancer 37 . A recent meta-analysis has shown that in North American and Asian women populations, high dietary consumption of vitamin A or supplements decreases the incidence of breast and ovarian cancers 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A deficiency can cause diseases such as decreased immunity, night blindness, dry skin, diarrhea, and certain cancers, including breast cancer 37 . A recent meta-analysis has shown that in North American and Asian women populations, high dietary consumption of vitamin A or supplements decreases the incidence of breast and ovarian cancers 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, vitamin A's role in breast cancer is complex, with mixed findings. High dietary vitamin A consumption correlates with decreased breast cancer incidence in North American and Asian populations [31]. The dysregulation of the retinoid signaling pathway is linked to tumor development.…”
Section: Vitamin Amentioning
confidence: 99%
“…Strategies for preventing the development of gynecologic cancers include regular gynecologic check-ups, human papillomavirus (HPV) vaccination or physical activity and a healthy diet [2,3]. In the past two decades, many publications have focused attention on the role of micronutrients in the prevention of gynecologic malignancies [4][5][6]. Extensive meta-analyses have shown that daily supplementation with vitamin A and D3 can reduce the incidence of ovarian cancer [7][8][9], as well as mortality from malignant cancer by up to 12% [9].…”
Section: Introductionmentioning
confidence: 99%